The "improper" feminine : the women's sensation novel and the new woman writing - Pykett, Lyn (Routledge, 1992)
The first comparative study of the women's sensation novel of the 1860s and the New Woman fiction of the 1890s, two genres which undermined the ideal of the `proper feminine' and dangerously put female sexuality on the literary agenda.